2014
DOI: 10.7739/jkafn.2014.21.2.162
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Learning Experiences and Self-Confidence of Core Nursing Skills in Nursing Practicum among Final Year Nursing Students

Abstract: This study was done to identify learning experiences and self-confidence and to analyze nursing students' self-confidence according to learning experiences for core nursing skills (CNS). Method: Participants were 502 final year nursing students. Data were collected using a structured questionnaire and analyzed using descriptive statistics and t-test. Results: Over 60% of participants had practiced 15 items of the 24 CNS in the basic nursing lab (BNL). In clinical practice (CP), they had practiced five items bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Numerous nursing educators and researchers have explored various ways to achieve this, and blended e-learning is emerging as an effective tool. 3,13,17,19,22,31 Implementation of blended e-learning has been found to yield improvements in psychomotor skills, such as clinical nursing skills, communication skills, and attitude, and was effective for physical assessment, interview skills, and patient education. 17 For example, McCutcheon et al 3 conducted a systematic review of educational methodologies for nursing students and reported that offering blended learning resulted in improved clinical skills over established face-toface instruction, a finding that is similar to the results of this study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Numerous nursing educators and researchers have explored various ways to achieve this, and blended e-learning is emerging as an effective tool. 3,13,17,19,22,31 Implementation of blended e-learning has been found to yield improvements in psychomotor skills, such as clinical nursing skills, communication skills, and attitude, and was effective for physical assessment, interview skills, and patient education. 17 For example, McCutcheon et al 3 conducted a systematic review of educational methodologies for nursing students and reported that offering blended learning resulted in improved clinical skills over established face-toface instruction, a finding that is similar to the results of this study.…”
Section: Discussionmentioning
confidence: 98%
“…Students are to be guided to establish skills as professional nurses and evaluate these skills so that they can solve problems by themselves and adequately perform nursing practices, 8,9 especially in emergency situations that require CPR and defibrillation. 10,25,31 Hence, in the present study, we examined the effects of blended e-learning, as a form of education that allows nursing graduates to better adapt to clinical settings and, more specifically, to provide proper nursing interventions for patients with cardiovascular problems, on student nurses' self-efficacy, problem solving, and psychomotor skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In‐class activities focused on case analyses with different clinical scenarios would be beneficial for top‐tier students who may want to explore more advanced topics. The level of confidence could also be influenced by numerous other factors such as the types and difficulty levels of core skills (Han, Cho, & Won, ). It is therefore necessary to investigate the effects of in‐class activities on confidence among students with differing levels of academic achievement, or using core skills of differing difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Advising students that they had made mistakes that they could not have been aware of may be detrimental to their confidence. Han et al () similarly found that participants in a simulation‐based practicum were less likely to become confident in performing skills than those who were not involved in the simulation, mainly due to the negative feedback given to the participants during the postsimulation video‐based debriefing session. Furthermore, the confidence in performing core skills among students involved in both flipped learning models increased between before the preclass session and after the actual clinical practicum, whereas it did not differ between the 2 groups after the practicum.…”
Section: Discussionmentioning
confidence: 99%